2018
DOI: 10.31681/jetol.378607
|View full text |Cite
|
Sign up to set email alerts
|

Flipped Classroom Model and Practical Suggestions

Abstract: Rapid changes in information and communication technologies have increased learners' expectations, which have caused researchers to search for new and effective ways of learning. In this respect, with the combined use of the advantages of both traditional learning models and distance education, use of blended learning models has become popular. The flipped classroom model, one of such blended models, has frequently been on the agenda in recent years. For the purpose of examining the applicability of the flippe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
(23 reference statements)
2
13
0
3
Order By: Relevance
“…They should be knowledgeable so that they can plan their instructional activities. This vehement requirement proves to be in symbiosis with teachers' technical competency that is strongly accentuated by many researchers (Arnold-Garza, 2014;Urfa, 2018;Vogelsang & Ollermann, 2019). Students also need to familiarize themselves with this approach to become active and responsible for their learning.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…They should be knowledgeable so that they can plan their instructional activities. This vehement requirement proves to be in symbiosis with teachers' technical competency that is strongly accentuated by many researchers (Arnold-Garza, 2014;Urfa, 2018;Vogelsang & Ollermann, 2019). Students also need to familiarize themselves with this approach to become active and responsible for their learning.…”
Section: Resultsmentioning
confidence: 99%
“…Yet, the very issue lies in teachers' mastery in preparing useful videos and tracking students' serious pursuits. In this context, Urfa (2018) showed that flipped learning popularity is due to its development of learners' academic achievement, satisfaction, motivation and active learning, but he maintained that the model requires educators' readiness and technical competency to prepare motivating videos and ensure that the learners watch them. The research literature showed that flipped classroom enhances students' motivation and many intertwined positive results.…”
Section: / 16mentioning
confidence: 99%
“…In the introduction phase, where students need some teaching materials so that they get to know materials that must be studied, students state that there is an increase in material that can be studied first before meeting the educator. In addition, educators have also started to make new habits with students, namely reading materials before online meeting with educators, so that students always learn materials first (URFA, 2018). This is also supported by the Brillian LMS which can inform the engagement of students.…”
Section: Discussionmentioning
confidence: 99%
“…Merak %33, konu %34'ü oluşturmaktadır (Ünsal, 2018). Bu yönüyle bakıldığında flipped öğrenme öğrencilerin akademik başarılarını artırmakta, dil becerilerin gelişimine katkı sağlamakta ve farklı öğrenme uygulamalarıyla öğrenciyi derse karşı motive etmektedir (Halili ve Zainuddin, 2015;Urfa, 2018). Motive olan öğrenci kendi hızında öğrenmesini gerçekleştirmektedir.…”
Section: Flipped öğRenme Uygulamalarının Etkililiğine İlişkin öğRetmeunclassified